PEMAHAMAN MATERI TERHADAP HASIL BELAJAR MAHASISWA PADA MATAKULIAH PRAKTEK - Mellasanti Ayuwardani (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
Practical lectures in their implementation require an understanding of how to carry out these activities. Not just knowledge, but understanding is needed. Lack of understanding can lead to inappropriate practicum results. The problem of this research is "How is the Effect of Understanding Material on Student Learning Outcomes in the typing basics practice course of the Semarang State Polytechnic Business Administration Department". The purpose of this study is the development of a conceptual integration model in understanding the material, to achieve maximum learning outcomes. The number of samples of this study were 89 respondents. The data collection method is done by giving a list of questions using Google Form. The t test results show that the Material Understanding variable has a t value of 11.522> t table 1.666 with a significance value of 0.000 <0.05, with an Adjusted R Square value of 0.810 or 81%. The conclusion in this study is that there is a positive and significant influence between Understanding Material on Learning Outcomes with an influence of 81%.